2021
DOI: 10.1042/etls20210213
|View full text |Cite
|
Sign up to set email alerts
|

It takes guts to learn: machine learning techniques for disease detection from the gut microbiome

Abstract: Associations between the human gut microbiome and expression of host illness have been noted in a variety of conditions ranging from gastrointestinal dysfunctions to neurological deficits. Machine learning (ML) methods have generated promising results for disease prediction from gut metagenomic information for diseases including liver cirrhosis and irritable bowel disease, but have lacked efficacy when predicting other illnesses. Here, we review current ML methods designed for disease classification from micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 135 publications
0
14
0
Order By: Relevance
“…Even though this does not necessarily represent a suboptimal result, it might indicate low generalisability of our model given the considerable drop in the AUC when the model faces an unprecedented dataset, perhaps owing to the model having been trained with a small training set. It has also been suggested that additional data, such as metabolomic or lifestyle-related information, combined with microbial data, might improve prediction accuracy [136], especially when performing disease prediction, something strongly linked to our case, taking the evidence regarding associations between HEI and obesity into account [118], [137], [138], as well as between HPF consumption and several pathologies.…”
Section: Discussionmentioning
confidence: 98%
“…Even though this does not necessarily represent a suboptimal result, it might indicate low generalisability of our model given the considerable drop in the AUC when the model faces an unprecedented dataset, perhaps owing to the model having been trained with a small training set. It has also been suggested that additional data, such as metabolomic or lifestyle-related information, combined with microbial data, might improve prediction accuracy [136], especially when performing disease prediction, something strongly linked to our case, taking the evidence regarding associations between HEI and obesity into account [118], [137], [138], as well as between HPF consumption and several pathologies.…”
Section: Discussionmentioning
confidence: 98%
“…Methods for identifying significant changes throughout a metagenome series is an active area of research (43). Currently, a common approach is to first simplify each metagenome into a profile that can be logically aligned and compared, such as taxonomic classification relative abundance, gene function presence, and counts of short sub-sequences (k-mers) (10). Yet, each of these strategies either oversimplifies potentially important sequences of microbial communities or is biased by a reference database (20; 25).…”
Section: Discussionmentioning
confidence: 99%
“…Although this might be a limitation derived from our small sample size, it should be noted that there is controversy over whether metagenomic data is enough to separate obese and lean patients [79]. Some authors argue that additional information, such as metabolomic or host genomic data, might be necessary [79,81].…”
Section: Discussionmentioning
confidence: 99%